KEBIJAKAN OTONOMI PERGURUAN TINGGI INDONESIA: ANTARA PRIVATISASI DAN KOMERSIALISASI - Diyanto, Chafid; Putranti, Ika Riswanti; Yuwono, Teguh; Yuniningsih, Tri (Universitas Islam Negeri Raden Intan Lampung, 2021)
The basic principle of the New Public Management (NPM) paradigm is to run state administration as it moves the business sector (run government like a business or market as a solution to the ills in the public sector). This strategy needs to be implemented so that the old model of bureaucracy that is slow, rigid and bureaucratic is ready to answer the challenges of the globalization era. The privatization of higher education in the form of PTN BH and BLU is an autonomous form of higher education institutions by adopting the values of NPM. In practice, there appears to be a shift and misunderstanding of the value of privatization which is interpreted as the commercialization of higher education. This article concludes that this higher education privatization policy has a negative impact, namely the commercialization of higher education, which if allowed to continue will grow the capitalization of education. Education can only be accessed by the owners of capital, while the lower class people are increasingly marginalized. Evaluation of the higher education privatization policy must be carried out immediately by the government in order to make improvements even if it is necessary to revoke and change the privatization policy of higher education.